Approximation of some classes of set-valued periodic functions by generalized trigonometric polynomials - Babenko, V. V.; Babenko, V. F.; Polishchuk, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We generalize some known results on the best, best linear, and best one-sided approximations by trigonometric polynomials from the classes of 2 π -periodic functions presented in the form of convolutions to the case of classes of set-valued functions.